2019
DOI: 10.1021/acs.langmuir.8b03785
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal-Substituted Krebs-Type Polyoxometalate-Doped PEDOT Films

Abstract: The transition metal-substituted Krebs-type polyoxometalates (POMs) [Sb 2 W 20 M 2 O 70 (H 2 O) 6 ] n− , M = Fe(III), Co(II), or Cu(II), were surface immobilized within the conducting polymer 3,4-ethylenedioxythiophene (PEDOT) on glassy carbon electrode surfaces. The immobilized films of different thicknesses were characterized by electrochemical and surfacebased techniques. The inherent redox activity for the Krebs-type POMs, [Sb 2 W 20 M 2 O 70 (H 2 O) 6 ] n− , M = Fe(III), Co(II), or Cu(II), that were obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Moreover, the detection of small mass variations which can be associated with specific fluxes to discriminate different steps of the doping‐dedoping process namely the participation of small cations. Naseer and co‐workers have fabricated and reported the electrochemical properties of transition metal‐substituted Krebs‐type POMs, [Sb 2 W 20 M 2 O 70 (H 2 O) 6 ] n− , M=Fe(III), Co(II), or Cu(II), immobilized within the conducting polymer PEDOT [27] . According to Chunchen Yuan et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the detection of small mass variations which can be associated with specific fluxes to discriminate different steps of the doping‐dedoping process namely the participation of small cations. Naseer and co‐workers have fabricated and reported the electrochemical properties of transition metal‐substituted Krebs‐type POMs, [Sb 2 W 20 M 2 O 70 (H 2 O) 6 ] n− , M=Fe(III), Co(II), or Cu(II), immobilized within the conducting polymer PEDOT [27] . According to Chunchen Yuan et al .…”
Section: Introductionmentioning
confidence: 99%
“…Naseer and co-workers have fabricated and reported the electrochemical properties of transition metalsubstituted Krebs-type POMs, [Sb 2 W 20 M 2 O 70 (H 2 O) 6 ] nÀ , M = Fe(III), Co(II), or Cu(II), immobilized within the conducting polymer PEDOT. [27] According to Chunchen Yuan et al a counter electrode made of SiW 11 -PEDOT hybrid film demonstrated an efficiency that was almost as high as that of DSSCs with Pt CEs. [28] Immobilization of POM redox centres in PEDOT hybrid film demonstrated improved charge propagation dynamics and potential applications in electrocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Integration as thin films remains a challenge. Their high solubility in water is an obvious problem which makes it impossible to obtain POMs as monolayers on water that can be transferred to a substrate as L-B films, and a significant amount of work has been channeled toward its advancement. However, a POM enclosed in an organic surfactant can be easily spread directly on water to form stable 2-D Langmuir monolayers . Xu et al studied Langmuir films of surfactant-encapsulated clusters (SEC) in which the cationic surfactant dimethyldioctadecylammonium (DODA) replaced the counter cations of Keggin-type polyoxometalate (POM) clusters, AW 12 O 40 z‑ (A, z = P, 3; Si, 4; B, 5; Co, 6).…”
Section: Introductionmentioning
confidence: 99%